The structure and development of turf hummocks in the Mesters Vig district, northeast Greenland - Raup, Hugh M. (Meddelelser om Grønland, 1965)
Turf hummocks in the Mesters Vig district of Northeast Greenland are composed primarily of mosses which form a substratum for several species of vascular plants. Well-defined, growing hummocks are found only on sites abundantly supplied with gently flowing surface water throughout most of the summer season. They may be common on drier sites, but here they are always in some stage of disintegration. They develop on any kind of soil, and on slopes of from 1 ° to 15°. They may or may not have upward projections of mineral soil beneath them. The vascular flora is characterized by the woody plants of the adjacent tundra, and by a few herbaceous species associated with them. Most of this flora is rooted in the turf, but a few species, notably Salix arctica, are firmly established in the mineral soil beneath, commonly with long horizontal taproots reaching far beyond the limits of the individual hummocks. Observations indicate that the hummocks begin their development with aquatic mosses. They begin to show appreciable enlargement only when more mesophytic mosses appear on them. These, in turn, occur only when " micro-elevations" appear above the general level of the surrounding, continually saturated surfaces. Such micro-elevations may be cobbles, small boulders, or local sand and silt deposits in shallow stream beds; they may be small moss polsters in extreme snow-bed environments; they may be upfrozen stones in fine-textured soils; they may be pre-existing microrelief features formed by gelifluction; or they may be due to normally irregular and slightly hummocky surfaces in the mats of aquatic mosses themselves. Most of the hummocks in the Mesters Vig district appear to have been initiated in the last of these various situations. A specific case of hummock development and deterioration is described in detail. A transect is analyzed, showing all stages from aquatic mosses to final disintegration and disappearance of the hummocks, with accompanying changes in water supply, insulation, frost action in the soils, and fauna! activity. Evidence is presented that individual plants of Salix arctica germinate on the hummocks during incipient stages of development, live through the entire sequence of growth and degradation, and survive long after the mosses have disappeared. Annual growth layers in these willows serve to calibrate the process, and by their variations indicate some of the major events in the sequence. The abundance of deteriorating hummocks in the Mesters Vig district, and of willows that show by their form that they have been through a hummock sequence, strongly suggests that many slopes have been subjected to recent desiccation, due largely to reduction of perennial snowdrifts. The age of the willows indicates that most of this desiccation has occurred within the last 75 years, a figure consistent with the recent general warming in the North Atlantic region.